AN INNOVATIVE TOOL FOR WORKING WITH PRESCHOOLERS USING A WEB-BASED SYSTEM (Education in the 21st Century, 2023)
Numerous studies show that the roots of many problems in a person's life go back to childhood. The problems of human self-affirmation, social role and adaptation in society are due to the characteristics of preschoolers.The mental structures of a child in preschool age, including personal ones, are in one holistic integrated state, in which it is difficult and, in principle, not correct to distinguish between different aspects of his psyche, since they are closely interconnected with each other.Preschool education is the cornerstone on which the quality of the child's further education depends.This makes the teacher's responsibilities. His task is not only to teach counting and writing, but also to lay a deep foundation in the child, to reveal his best qualities, to show the ways of educational activity. The latter is especially relevant in today's rapidly changing, information-flooded world. It is necessary to teach the child to work with information, teach to learn.In preschool age, the child begins to recognize the similarities, differences, shapes and sizes of objects based on their characteristics. In this regard, when working with preschoolers, it is necessary to create an environment in which the newly acquired personal qualities of these children will develop: independence, the desire to learn something new, curiosity.From this age, it is necessary to actively develop the child's bold creativity and imagination, attention and thinking. Children mainly perceive through the senses, so it is necessary to organize games that will be visual, sensory, didactic.Problem. A fundamental change in the nature of education in the information age is closely associated with the spread of modern information and communication. The problem of ICT development and development in education is especially relevant for developing or less developed countries. Can countries fighting poverty and underdevelopment afford to wasteful speculation on the use and diffusion of ICT in education, spending huge sums of money on such programs?In addition, most post-Soviet countries, including Armenia, have special problems. A sufficiently high level of education, societies with traditions are obliged to carry out fundamental reassessments and changes at71different levels of education. On the other hand, in the Republic of Armenia there has been a transition to universal inclusion at all levels of education, and all this raises questions.1. How ICT is used to work with preschool children?2 ․ How do they affect the overall development of preschoolers?These questions are at the center of attention of many modern researchers who consider them from psychological, medical, technical and pedagogical points of view.Purpose. The aim of our research is to develop and test an electronic web system that can be used in the process of ensuring the general development of preschoolers.Research novelty. In order to make the interaction between the child and the teacher more interesting, interactive, has developed an electronic web-based system to support the overall development of preschool children, unique of its kind in the Armenian reality, easy to use and provides high efficiency.
Keywords: preschool education, information and communication technologies, general development, ICT tools, education, upbringing.